Meningkatkan Hasil Belajar Melalui Media Benda Asli Pembelajaran IPA di Kelas IV SD Negeri Tingkulang Kecamatan Tomini Kabupaten Parigi Moutong - Laganing, Najamuddin; Paudi, Ritman Ishak; Nur’ain, Nur’ain (Jurnal Kreatif Online, 2013)
The study, entitled Improving Learning Outcomes by Original Media Learning Objects IPA SDN Tingkulang the District IV Class Tomini Moutong Parigi District. Subjects numbered 21 students consisting of 12 girls and 9 boys . The data taken was qualitative and quantitative data. Cycle I obtained 38.09% Mastery Learning Classical classical absorption 49.4%, activity of teachers in the category of very less average percentage of 54.5% and the activity of students in the category of very less average percentage of 45% . Learning outcomes of students in the second cycle was obtained mastery learning classical increased to 90.4 % classical absorption increased to 82.3% , the activity teachers are in very good category is 95.4% and the activity of students in a category very well with the average percentage 95%. Classical completeness in the second cycle of research has met success indicators, namely 80%, it can be concluded that the original object of media can improve learning outcomes Tingkulang Elementary School fourth grade .